Students-Led Religious Activism in Nigeria: A Study of MSSN Rivers State Area Unit Port Harcourt (Al Basirah, 2025)
The Muslim Students’ Society of Nigeria (MSSN), founded in 1954, has played a notable role in shaping Islamic identity among Nigerian youths. It has branches in every state called Area Unit. The Rivers State Area Unit - where Muslims constitute a minority— was established in 1984 by one Misbahudin Nurudin during his National Youth Service Corps (NYSC) posting. The organization has been active in various religious, educational, and advocacy initiatives. Although several research articles and reports have been published stating the condition of Muslims living in Nigeria, Some have focused on role of The Muslim Students' Society of Nigeria MSSN as well, but The MSSN Rivers State Area Unit still remain unexamined. This study explores the historical evolution, organizational structure, and operational strategies of the MSSN Rivers State Area Unit. It asks: How has the MSSN responded to the challenges of religious minority status in Port Harcourt? What mechanisms has it employed to sustain Islamic consciousness and student activism in a context of limited institutional support? Adopting a historical-analytical method and drawing on oral interviews and primary documents, the research investigates the key turning points, leadership transitions, and institutional engagements that have defined the Unit's trajectory. It considers both internal and external factors—such as member instability, financial constraints, and religious tensions—and examines how these have shaped the society’s programs and resilience. By focusing on the MSSN’s localized experience in Port Harcourt, the study contributes to broader conversations on youth-led religious activism in pluralistic societies and the role of faith-based student organizations in shaping collective identity under marginal conditions. The key finding of the research is that MSSN plays a vital role in propagating Islam and uplifting Muslim community in Nigeria. This article recommends that the efficiency of the MSSN local units can increase by strengthening the organizational structure of the units, searching new financial avenues, building strong alumni networks and emphasizing educational and spiritual growth of the members.
Keywords: Muslim Students’ Society; MSSN; Islamic Resurgence; Port Harcourt; Nigeria